The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s11255-006-9071-z
|View full text |Cite
|
Sign up to set email alerts
|

Elevated urinary cytokine levels in patients undergoing ileal neobladder replacement compared with sigmoid neobladder replacement

Abstract: These findings suggest that chronic inflammation was more frequently observed in patients with ileal neobladder than in those with sigmoid neobladder, and that IL-6 and IL-8 were involved in persistent bacteriuria in patients with ileal and sigmoid neobladder, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Nakano et al found that the level of urinary pro-inflammatory interleukin-1b, interleukin-6 and interleukin-8 in IN patients was greater than in patients with SN, and this enhanced production was associated with chronic bacteriuria. 29 This signifies that the sigmoidal mucosa can better bear the burden of chronic inflammation caused by chronic urine contact.…”
Section: Discussionmentioning
confidence: 99%
“…Nakano et al found that the level of urinary pro-inflammatory interleukin-1b, interleukin-6 and interleukin-8 in IN patients was greater than in patients with SN, and this enhanced production was associated with chronic bacteriuria. 29 This signifies that the sigmoidal mucosa can better bear the burden of chronic inflammation caused by chronic urine contact.…”
Section: Discussionmentioning
confidence: 99%